The Effect of Using 3D Pageflip Learning Media on Student Learning Outcomes in Vibration and Wave Material - Tirtawaty Abdjul; Nurhayati; Nancy Katili; Nova Elysia Ntobuo (Jurnal Penelitian Pendidikan IPA, 2023)
One learning media that can be applied in the learning process is 3D Pageflip Professional. 3D Pageflip Professional is a leading application software for creating e-books, digital magazines, e-papers, and others. This research aims to describe the effect of using 3D Pageflip Professional learning media on vibration and wave material at SMP Negeri 1 Telaga Jaya. This research uses a valid experimental method with a posttest-only control design. The sampling technique in this research was random sampling. The sample for this research was class VIII students divided into two classes, namely the experimental class is class VIII-1, and the control class is class VIII-2. This research uses quantitative descriptive data analysis. The research showed that the average percentage of cognitive level scores for student learning outcomes in classes using 3D Pageflip Professional learning media reached 81.30% (very high). In types using PowerPoint media, it reached 78.33% (high). Likewise, the results of classical completion in learning activities were 92% in the experimental class and 85% in the control class. These values ​​show that the 3D Pageflip Professional learning media influences the learning outcomes of class VII students at SMP Negeri 1 Telaga Jaya, especially on vibration and wave material.